Integration of Pancasila Values in Islamic Cultural History Subjects: A Content Analysis - Faaza, Muhammad; Rofik, Rofik (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – This study aims to determine Pancasila's values, which are integrated into student books for class X Islamic Cultural History. Design/methods/approaches – To collect data, this library research uses documentation. The data is collected from relevant sources such as student books, journals, news, and related laws and regulations. Data analysis was performed using the content analysis method. Findings – The results of this study indicate that the Islamic Cultural History student book at Madrasah Aliyah Class X contains Pancasila values that can be integrated with the material. It shows that 1) there are 17 Pancasila values contained in the Islamic Cultural History MA student book for class X, namely in the first precepts points 1, 2, and 7; the second precept of the 9th, 10th, 11th, 13th, 14th, and 15th points; the third precept point 18 and 19; the fourth point of the 27th precept; fifth precept on points 37,40, 41, 42, and 45. 2) Integrating the values of Pancasila with the material in the Islamic Cultural History MA Class X student book is expected to be able to increase the spirit of nationalism and be able to prevent the spread of anti-Pancasila ideology, which is currently rife in Indonesia, especially among Muslim students because Pancasila is the foundation for Islamic Religious Education in Indonesia, especially the History of Islamic Culture to maintain national unity and integrity. Research limitations – This research has limitations in scope, it can only cover available sources, so it may not include all relevant literature. Originality /value – Teachers can use the findings from the research in teaching Islamic cultural history subjects that integrate with Pancasila values.